2018
DOI: 10.1038/s41598-018-27375-4
|View full text |Cite
|
Sign up to set email alerts
|

Toxic anthropogenic signature in Antarctic continental shelf and deep sea sediments

Abstract: Industrial activity generates harmful substances which can travel via aerial or water currents thousands of kilometers away from the place they were used impacting the local biota where they deposit. The presence of harmful anthropogenic substances in the Antarctic is particularly surprising and striking due to its remoteness and the apparent geophysical isolation developed with the flows of the Antarctic Circumpolar current and the ring of westerly winds surrounding the continent. However, long-range atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…The cytotoxic activity in marine sediment extracts has been studied using different cell lines (Caballero-Gallardo et al, 2015 ; Isla et al, 2018 ; Kocan et al, 1985 ). A reduction in cell viability (26–48%) was observed in cells exposed to 1% extracts from stations S2, S3, S4, S15, S6, and S9.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxic activity in marine sediment extracts has been studied using different cell lines (Caballero-Gallardo et al, 2015 ; Isla et al, 2018 ; Kocan et al, 1985 ). A reduction in cell viability (26–48%) was observed in cells exposed to 1% extracts from stations S2, S3, S4, S15, S6, and S9.…”
Section: Discussionmentioning
confidence: 99%
“…The Antarctic is an environmental sink for anthropogenic bio-accumulative POPs and heavy metals, reaching atmospheric, marine (from sea surface to the deep sea) and terrestrial environments (Isla, Pérez-Albaladejo & Porte, 2018). Biomagnification of toxic polychlorinated biphenyls (PCBs) has been reported across marine foodwebs.…”
Section: (D) Sentinel Species and Communities Warn Of Environmental Changesmentioning
confidence: 99%
“…van den Brink et al 120 found decreasing trends in PCBs, HCB and dieldrin levels in Adélie penguins, southern fulmars and pelagic fish from 1993–1994 to 2003–2004, even though their concentrations were steady or increasing in benthic organisms; thus, they questioned whether the POPs contamination in Antarctica is actually declining. Isla et al 121 detected cytotoxic activity in extracts of marine sediments collected along thousands of kilometers of the Antarctic continental shelf and up to 1200 m depth. However, some more recent works would seem to indicate a decreasing trend of long-range transport and bioavailability of POPs in the Antarctic environment.…”
Section: Introductionmentioning
confidence: 99%